Ben Fletcher et les IWW sur les quais de Philadelphie. Un modèle de syndicalisme interracial au début du 20e siècle - Peter Cole (Cahiers d’histoire.)
Now forgotten, Ben Fletcher ranks among the most important African Americans unionists and revolutionaries in U.S. history. In 1913, Fletcher helped create Local 8 of the Industrial Workers of the World (IWW), perhaps America’s most radical union. Local 8 represented a workforce one-third Black, one-third Irish American, and one-third European immigrant. Fletcher and other Wobblies believed that what united Black and white workers was more important than their racial differences, and that the best way to help Black workers was through interracial unionism—a class-based solution to racially-linked problems. He did so in an era of rampant racism, anti-unionism, and xenophobia and without signing a contract, preferring to enforce their demands via the ever-present threat of a strike. In short, Fletcher and a bunch of so-called “unskilled” working-class Black and white men, native-born and immigrant, managed to do what few American institutions have yet achieved: equality and integration.